Improve electromagnetic compatibility of electronic products with multivariate parametric design. Issue 1 (3rd January 2017) - Huang, Chien-Yi; Chen, Ching-Hsiang
Abstract : Purpose: Differing from previous studies trying to solve the electromagnetic compatibility (EMC) issue by addressing single factor, this study aims to combine measures of shielding, filtering and grounding to design parameters with the Taguchi method at the beginning of product design to come up with the optimal parameter combination. Design/methodology/approach: EMC-related performance such as radiated emission, conduction interference and electrical fast transient/burst immunity (EFT) are response variables, whereas the printed circuit board and mechanic design-relevant parameters are considered as control factors. The noise factors are peripherals used together with the tablet. Findings: The optimal design parameter matrix based on results from the application and integration of multivariate analysis method of principal component grey relation and technique for order preference by similarity to ideal solution suggests 14 grounding screw holes, cooling aperture of casing at diameter of 3 mm and staggered layout and 300O filter located at source of noise. Validation of this matrix shows around 10, 1 and 8 per cent improvement in radiation, conduction interference and EFT immunity. Originality/value: The multivariate quality parameters' design method proposed by this study improves EMC characteristics of products and meets the design specification required by customer, accelerating electronic product research and development process and complying with electromagnetic interference test regulations set forth by individual country.